Предмет: Алгебра, автор: alllexWen

Упростите выражение
a) (x-3)(x-5)-2x(x-4)
б) 4a(a-6)-(a-12)^2
в) (m+5)^2-10m

Ответы

Автор ответа: anywaythanks
1

a)(x - 3)(x - 5) - 2x(x - 4) =   ( {x}^{2}  - 5x  - 3x + 15) - (2 {x}^{2}  - 8x) =       15 -  {x}^{2}

b)4a(a - 6) - (a - 12) {}^{2}  =   4 {a}^{2}  - 24a - ( {a}^{2}  - 24a  + 144) = 3 {a}^{2}  + 144

c)(m + 5) {}^{2}  - 10m = ( {m}^{2}  + 10m + 25) =  {m}^{2}  + 25

Автор ответа: sakuyaize
0

1.(x-3)(x-5)-2x(x-4)=

 {x}^{2}  - 5x - 3x + 15 - 2 {x}^{2}  + 8x

=

  - {x}^{2}  + 15

2.

 {4a(a-6)-(a-12)}^{2}

4 {a}^{2}  - 24a -  {a}^{2}  + 24a - 144

3 {a}^{2}  - 144

3.

( {m + 5)}^{2}  - 10m

 {m}^{2}  + 10m + 25 - 10m

 {m}^{2}  + 25

Похожие вопросы
Предмет: Физика, автор: vaduk1234
Предмет: Физика, автор: VladimirAnohov